Model analysis of carbon fiber reinforcement properties for reinforced concrete beams to resist blast loads - Al-Jasmi, Salah; Nur Farhayu, Ariffin; Mazlan, Abu Seman (Elsevier Ltd, 2023)
Safety is paramount in Oil & Gas plants, and continuous monitoring and improvements ensure that all measures are taken to protect them. The purpose of this paper is to examine how composite materials can be used to improve the structural reinforcement of concrete beams. Concrete structural beams have been improved in the past by using varying Fiber Reinforced Properties (FRP). It has been investigated how Carbon Fiber Reinforced Properties (CFRP) composites perform under blast loads and how they behave, respond, and perform as reinforcement for reinforced concrete beams. The response of RC beams to blasts was analyzed using a software modelling program called ANSYS that can mimic RC beam properties when reinforced with CFRP in concrete structures. The reason CFRP was chosen was because its properties showed great potential and it is well suited for testing and analysis. As well as absorbing a lot of energy, this material is strong, elastomeric, and alkali-resistant. A numerical analysis and model analysis have been performed with the help of the ANSYS software program. In the experimental results, CFRP was found to increase the flexural and shear strength of RC beams. The RC beams reinforced with CFRP has outperformed RC beam (control beam) in factors such as in Deformation, Equivalent Stress, and Shear Stress by a minimum percentage difference of 0.784% and maximum of 7.09% depending on the layers of CFRP and load applied on the beams in each factor.